The effects of seasonally variable dragonfly predation on butterfly assemblages. Issue 1 (1st January 2013) - Tiitsaar, Anu; Kaasik, Ants; Teder, Tiit
Abstract : Where predation is seasonally variable, the potential impact of a predator on individual prey species will critically depend on phenological synchrony of the predator with the prey. Here we explored the effects of seasonally variable predation in multispecies assemblages of short‐lived prey. The study was conducted in a landscape in which we had previously demonstrated generally high, but spatially and seasonally variable dragonfly‐induced mortality in adult butterflies. In this system, we show that patterns of patch occupancy in butterfly species flying during periods of peak dragonfly abundance are more strongly associated with spatial variation in dragonfly abundance than patch occupancy of species flying when dragonfly density was low. We provide evidence indicating that this differential sensitivity of different butterfly species to between‐habitat differences in dragonfly abundance is causally tied to seasonal variation in the intensity of dragonfly predation. The effect of dragonfly predation could also be measured at the level of whole local butterfly assemblages. With dragonfly density increasing, butterfly species richness decreased, and butterfly species composition tended to show a shift toward a greater proportion of species flying during periods of off‐peak dragonfly abundance.